Sexual Violence against Women: A Study of Struggling and Negotiation of Raped Ethnic Women - Yangyubon, Netdao (วารสารสันติศึกษาปริทรรศน์ มจร, 2020)
This research article has 2 objectives: 1) to find out conditions and contexts which facilitate sexual violence against marginalized ethnic women as well as the effects of rape occurring in marginalized ethnic women; and 2) to find out how raped ethnic women are able to overcome trauma and negotiate with the family and community. The research methodology consists of 3 methods; 1) the participatory observation by joining daily life activities with key informants; 2) in-depth interviews with key informants; and 3) interviews with representatives of NGOs and governmental officers. The units of analysis consist of narratives of the raped ethnic women to understand how structural conditions subjugate raped ethnic women as well as how these women have struggled or negotiated in their life. From the research, it is found that: 1) the rape of the ethic women is a form of sexual violence derived from multiple factors; politics, government, justice process, economics and culture that affected the victims’ daily lives. The violence overlaid with ethnicity, gender, labor migration, and unequal power of negotiation that repeatedly jointly produced the violence as normal phenomenon, and 2) new identities of the raped women could be built up as survivors by use of the NGOs mechanism in struggling in the justice process, and use of various kinds of capitals such as being good mothers, grateful daughters, being wealthy status, etc., to negotiate with their family, community and others to overcome the trauma and survive worthily in the society.